Toxoplasmic Encephalitis and Hyper-IgM Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A 9-year-old boy with hyper-IgM syndrome complicated by impaired consciousness and disseminated toxoplasmosis is reported from Nagoya University School of Medicine, Japan.